The Effect of Proposed Training Program For Developing Response Speed and Shooting Accuracy in VIP's Bodyguards - Abdul Karim, Eimad (Journal of Physical Education, 2016)
Due to the increase in assassinations and assaults on very important persons VIPs and the great increase in crime and organized crime, it became necessary to develop security systems. VIPs protection is one of the most important systems in the field of fighting organized crime. VIP protection is responsible for guarding important local and foreign persons inside the country. The aim of the research is to identify the speed of response in shooting accuracy of VIP bodyguards. The researchers hypothesized statistical differences between pre and posttests on shooting accuracy in favor of the experimental group. They used the experimental method with two groups; experimental and controlling groups. The researchers concluded that bodyguards needed three hours of training per day; the first for improving fitness, the second for mortal combat, and the third bodyguard duties as well as developing other traits. Finally the researchers concluded a strong relationship between speed and strength